EVALUASI FASILITAS PERENCANAAN WILAYAH PADA JEMBATAN BARELANG DALAM MENDUKUNG PENGEMBANGAN WILAYAH DI KOTA BATAM - Cholin Cholin; Yuanita FD Sidabutar (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to evaluate the regional planning of the Barelang Bridge development in supporting regional growth in Batam City. A quantitative approach was employed using a survey method involving 20 respondents through a five-point Likert scale questionnaire consisting of 12 indicators. Data were analyzed using mean scores, variance analysis, Cronbach’s Alpha reliability test, and SWOT analysis to identify internal and external factors. The findings indicate that public perception of the Barelang Bridge is generally positive, with mean scores ranging from 3.65 to 4.10. The bridge significantly enhances inter-regional connectivity, improves mobility of goods and services, stimulates economic growth, and creates development opportunities in Rempang and Galang areas. The reliability test resulted in a Cronbach’s Alpha value of 0.9744, indicating excellent internal consistency. SWOT analysis reveals that strategic geographical location and government support constitute major strengths, while development disparities and limited supporting infrastructure remain key weaknesses. Industrial and tourism development opportunities are substantial; however, social conflicts and environmental degradation pose potential threats. Therefore, sustainable, participatory, and integrated regional planning strategies are required to optimize equitable development outcomes.